Urban Sprawl Control Efforts Based on Land Prices in Driyorejo District, Gresik Regency - Rahma Novi Chamima; Linda Dwi Rohmadiani (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2025)
The purpose of this study is to determine the level of urban sprawl development from 2016 to 2020, the influence of land prices on urban sprawl development and urban sprawl control efforts in Driyorejo District based on land prices. The analysis methods used are spatial analysis, scoring, linear regression and AWOT. Data collection techniques were observation, questionnaires, documentation and agency surveys. The results showed that there was only 1 village that experienced a decrease in the level of urban sprawl from 2016-2020, namely Randegansari Village. The development of urban sprawl level in Driyorejo Subdistrict has no significant relationship with land price, but is influenced by other factors. Efforts to control urban sprawl based on the results of the AWOT analysis that the local government needs to compile and implement the Detailed Spatial Plan and Zoning Regulations of Driyorejo District based on applicable regulations and improve connectivity and accessibility between regions.